2010
DOI: 10.1007/s11595-010-1012-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-isothermal melt crystallization kinetics of anhydrite-filled polypropylene composites

Abstract: Fig.5 Plots of ln(-ln(1-X t )) vs lnφfor PP and composite during non-isothermal crystallization process PP/anhydrite: (a) 100/0, (b) 90/10, (c) 80/20, (d) 70/30 Vol.25 No.1 WANG Shaohui et al: Non-isothermal Melt Crystallizatio…

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Figure 5 and Table 2 showed that the exothermic trace of the two samples became wider, the crystallization peak temperature( T p ) shifted to lower temperature and the crystallization exothermic heat became smaller as the cooling rate increased which are identical with the conclusion drawn by Zhang et al [10], Wang et al [11], and Supaphol et al [12]. This can be explained that at high cooling rate, there is an abrupt increase in polymer melt viscosity, i.e., the moving ability of the segments became worse, thus, the segments need longer time to enter the lattice, so T p shifted to lower temperature.…”
Section: Resultssupporting
confidence: 83%
“…Figure 5 and Table 2 showed that the exothermic trace of the two samples became wider, the crystallization peak temperature( T p ) shifted to lower temperature and the crystallization exothermic heat became smaller as the cooling rate increased which are identical with the conclusion drawn by Zhang et al [10], Wang et al [11], and Supaphol et al [12]. This can be explained that at high cooling rate, there is an abrupt increase in polymer melt viscosity, i.e., the moving ability of the segments became worse, thus, the segments need longer time to enter the lattice, so T p shifted to lower temperature.…”
Section: Resultssupporting
confidence: 83%
“…25 If the p-n junction is the working junction, the V oc should be determined by the difference between the Fermi level of the nanocrystals and TiO 2 . 32 In order to make a sound comparison, polymers with different HOMO levels and nanocrystals with different Fermi levels are selected. Fig.…”
Section: Resultsmentioning
confidence: 99%